Selecting Optimal Technologies for Ballast Water Treatment - Šateikienė, Diana; Stanelytė, Daiva (Jaunųjų mokslininkų darbai, 2016)
Nowadays one of the most serious problems in the marine environment is the spread of invasive species through ships’ ballast water. Ballast water treatment is one of preventive measures aimed at solving this problem. Mechanical, physical and chemical methods for ballast water treatment have been overviewed in the paper. All methods must ensure that the natural environment and human health are protected, especially when chemical substances are used – they must be safely stored to prevent any accidental contamination of the environment. Released ballast water must be clean, without chemical contaminants, its characteristics unchanged. The parameters that affect the effectiveness of water treatment have been identified. The effects of chlorine on the environment, ship construction and nature have been described, the ways of reducing damage are provided. The principle of evaluating chlorine concentration, which depends on the characteristics of ballast water, is provided.